IMPLEMENTATION OF HEALTH EDUCATION USING AUDIO-VISUAL MEDIA ON PERINEAL WOUND CARE IN POSTPARTUM MOTHERS WITH KNOWLEDGE DEFICIT PROBLEMS IN THE ROSE ROOM RSI JEMURSARI SURABAYA - Wati, Reni Dwi Novita; Kamariyah, Nurul; Afiyah, R. Khairiyatul; Ainiyah, Nur (Universitas Nahdlatul Ulama Surabaya, 2024)
Introduction: The problem that often occurs in postpartum mothers is the lack of knowledge of mothers in caring for perineal wounds. Objective: The purpose of this study was to analyze nursing care for postpartum mothers by providing education through audio-visual media about perineal wound care to overcome knowledge deficits. Methods: The research design uses a case study; the subject of this research is Mrs. R with knowledge deficit nursing problems. The case study was carried out on December 26-27, 2022, with a data collection method covering assessment to evaluation by means of anamnesis, physical examination, and observation. The research location was carried out in the Rose Room of RSI Jemursari Surabaya. Results: The results obtained after providing education through audiovisual media about perineal wound care at Mrs. R for 2 days were that the client's knowledge was getting better, verbalization of interest in learning increased, the ability to explain knowledge about a topic increased and questions about the problems faced increased. Conclusions: Case studies show that education through audiovisual media can overcome knowledge deficits in postpartum mothers about perineal wound care. It is expected that health workers will apply the provision of education through audiovisual media to postpartum mothers who experience a deficit of knowledge.